Pressure Injury Surveillance and Prevention in Australia: Monash Partners Capacity Building Framework - Team, Victoria; Jones, Angela; Teede, Helena; Weller, Carolina D. (Frontiers in Public Health, 2021)
A hospital-acquired pressure injury (HAPI) is a common complication across the globe. The severity of HAPI ranges from skin redness and no skin breakdown to full skin and tissue loss, exposing the tendons and bones. HAPI can significantly impact the quality of life. In addition to the human cost, this injury carries a high economic burden with the cost of treatment far outweighing the preventative measures. The HAPI rates are a key indicator of health services performance. Globally, healthcare services aim to reduce its incidence. In Australia, the federal health minister has prioritised the need for improvement in HAPI surveillance and prevention. Capacity building is vital to optimise pressure injury (PI) surveillance and prevention in acute care services. In this perspective article, we provide a framework for capacity building to optimise HAPI prevention and surveillance in a large cross-sector collaborative partnership in Australia. This framework comprises six key action areas in capacity building to optimise the HAPI outcomes, such as research, organisational development, workforce development, leadership, collaboration, and consumer involvement.